Lack of serological and molecular evidences of Zika virus circulation in non-human primates in three states from Brazil - Haisi, Amanda [UNESP]; Wu, Stacy; Zini, Nathalia; Silva, Maria Luana Cristiny Rodrigues da; Malossi, Camila Dantas [UNESP]; Cubas, Zalmir Silvino; Cubas, Patricia Hoerner; Teixeira, Rodrigo Hidalgo Friciello; Sousa, Monica Shinneider de; Lucena, Ricardo Barbosa; Svoboda, Walfrido Kuhl; Osaki, Silvia Cristina; et al. (Fundaco Oswaldo Cruz, 2022)
BACKGROUND Zika virus (ZIKV) was discovered in 1947 with the virus isolation from Rhesus monkey (Macaca mulatta) in Uganda forest, Africa. Old World Primates are involved in a sylvatic cycle of maintenance of this arbovirus, however a limited knowledge about the role of New World primates in ZIKV transmission cycles has been established. OBJECTIVE This work aimed to investigate the presence of enzootic circulation of ZIKV in New World Primates from three Brazilian states: Sao Paulo, Paraiba, and Parana. METHODS We analyzed 100 non-human primate samples collected in 2018 and 2020 from free-ranging and captive environments from Sao Paulo (six municipalities belonging to Sorocaba region), Paraiba (Joao Pessoa municipality), and Parana (Foz do Iguacu municipality) using reverse transcriptase quantitative polymerase reaction (RT-qPCR) assays, indirect enzyme-linked immunosorbent assay (ELISA), and plaque reduction neutralization test (PRNT). FINDINGS All samples (n = 141) tested negative for the presence of ZIKV genome from tissue and blood samples. In addition, all sera (n = 58) from Foz do Iguacu' non-human primates (NHPs) were negative in serological assays. MAIN CONCLUSION No evidence of ZIKV circulation (molecular and serological) was found in neotropical primates. In addition, the absence of antibodies against ZIKV suggests the absence of previous viral exposure of NHPs from Foz do Iguacu-PR.
Keywords: Arbovirus; Non-human primates; Public health; Sylvatic cycle